PENGARUH DISIPLIN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA UNIT KERJA BIRO SDM DAN UMUM PERPUSTAKAAN NASIONAL RI KOTA JAKARTA PUSAT - Fauzi Novrizal; I Gede Marendra (Journal of Research and Publication Innovation, 2025)
The aim of this research is to determine "The Influence of Discipline and Work Motivation on Employee Performance in the Work Unit of the HR and General Bureau of the National Library of the Republic of Indonesia, Central Jakarta City". The research method used is a quantitative method. The sampling technique uses a saturated sample with a population of 79 respondents. The discipline for this research shows the regression equation Y = 32.201 + 0.205 Hypothesis testing obtained a value of tcount > ttable or (3.819 > 1.991). So H0 is rejected and H1 is accepted, meaning that there is a significant influence between discipline and employee performance. Work motivation shows the regression equation Y = 37.371 + 0.057 Hypothesis testing obtained a value of tcount < ttable or (0.567 < 1.991). So H0 is accepted and H2 is rejected, meaning that there is no significant influence between work motivation and employee performance. Simultaneously shows the regression equation Y = 36.402 + 0.242X1 – 0.137X2, the correlation coefficient is 0.422, which means the two variables have a moderate or quite strong level of relationship, with a determination value of 0.178 or 17.8%. Hypothesis testing obtained a value of Fcount > Ftable or (8.229 > 3.12) so that H0 was rejected and H3 was accepted, meaning that there was a significant simultaneous influence between Discipline and Work Motivation on Employee Performance in the HR and General Bureau Unit of the National Library of Indonesia, Central Jakarta City.